Scope of Re-incorporation of Selected Medicinal Plants in Forest Ecosystems - Raina, R.; Mehra, T. S. (Indian Forester, 2011)
Approach to conserve biodiversity for sustainable development should be targetted at different levels, from improving living standards to changing the attitude of people. If Himalayan medicinal plants are to continue to serve the needs of the people without being reduced to a dangerously unstable resource base, they have to be considered in the perspective of sound ecological management that also has economic benefits to the local people. From the concept of in-situ conservation we need to move to In-situ cultivation.